Factors contributing to delay in diagnosis of Guillain‐Barré syndrome and impact on clinical outcome. Issue 3 (8th August 2015) - Dubey, Divyanshu; Kapotic, Marissa; Freeman, Matthew; Sawhney, Anshudha; Rojas, Julio C.; Warnack, Worthy; Vernino, Steven
ABSTRACT: Introduction: Heterogeneity of presenting symptoms makes the initial clinical diagnosis of Guillain‐Barré syndrome (GBS) challenging. Methods: Observational retrospective study from 2 teaching hospitals (Parkland Memorial Hospital and University of Texas Southwestern University Hospital) between 2008 and 2013. Results: Sixty‐nine GBS patients were identified. GBS was suspected on initial emergency department visit in only 49%. During first hospital encounter, 58% were evaluated by a neurologist. Neuropathic pain and presence of intact deep tendon reflexes were associated with delayed GBS diagnosis ( P < 0.05). There was significantly better clinical outcome among patients who were evaluated by a neurologist during the initial visit ( P < 0.005). Among these patients there was also significant difference in discharge destination; 71.2% of patients evaluated by a neurologist were discharged home ( P < 0.01). Patients in whom GBS was not suspected at the time of initial Neurology evaluation were more likely to require intubation and to have residual weakness at the time of discharge ( P < 0.05). Conclusions: Atypical clinical signs and symptoms may lead to delayed diagnosis of GBS. Early neurological evaluation is associated with improved clinical diagnosis and discharge disposition. Muscle Nerve 53: 384–387, 2016